Epigenetic Measurement of Key Vertebrate Population Biology Parameters - Heydenrych, Matthew J.; Saunders, Benjamin J.; Bunce, Michael; Jarman, Simon N. (Frontiers in Ecology and Evolution, 2021)
The age, sex, and sexual maturity of individual animals are key parameters in assessing wild populations and informing conservation management strategies. These parameters represent the reproductive potential of a population and can indicate recovery rates or vulnerabilities. Wild populations are difficult to study; logistically, economically, and due to the impacts of invasive biomonitoring. Genetic and epigenetic analyses offer a low impact, low cost, and information-rich alternative. As epigenetic mechanisms are intrinsically linked with both biological aging and reproductive processes, DNA methylation can be used as a suitable biomarker for population biology study. This review assesses published research utilising DNA methylation analysis in relation to three key population parameters: age, sex, and sexual maturity. We review studies on wild vertebrates that investigate epigenetic age relationships, with successful age estimation assays designed for mammals, birds, and fish. For both determination of sex and identification of sexual maturity, very little has been explored regarding DNA methylation-based assays. Related research, however, confirms the links between DNA methylation and these processes. Future development of age estimation assays for underrepresented and key conservation taxa is suggested, as is the experimental development and design of DNA methylation-based assays for both sex and sexual maturity identification, further expanding the genomics toolkit for population biology studies.